Readability Evaluation for Ukrainian Medicine Corpus (UKRMED) - Cherednichenko, Olga; Kanishcheva, Olga (My University, 2021)
In our work, we decided to demonstrate how to work different readability formulas on our Ukrainian-language corpus (UKRMED) of medical texts. UKRMED contains three types of texts in the medical domain divided by their complexity: “Complex texts”, “Moderate texts”, and “Simple texts”. This research aims to (1) demonstrate the use of the most commonly used readability formulas on written health information in Ukrainian, (2) compare and contrast these different formulas to various texts (simple, complex, and moderate), (3) research different medical text features which will be used for text simplification and classification medical texts and (4) prepare recommendations for using these formulas to the evaluation of readability medical texts in Ukrainian.
Keywords: text simplification; readability formulas; reading indexes; medicine text corpus; Ukrainian